TALC PLEURODESIS IN MANAGING BREAST CANCER-CAUSED MALIGNANT PLEURAL EFFUSIONS - Stevanović, Stefan; Milojković, Miloš; Petrović, Jelena; Đorđević, Nikola (Sanamed, 2025)
Introduction: Breast cancer (BC) is the most common malignant tumor and the leading cause of cancer-related deaths among women in Serbia. Malignant pleural effusion (MPE) is a common manifestation of metastatic BC. Among solid tumors, BC accounts for the second-highest prevalence of MPE, occurring in 25% of cases. Current guidelines identify talc pleurodesis (TP) as one of the most effective treatments for MPE in most patients. This study aims to evaluate the effectiveness of TP in managing breast cancer-caused MPE.Patients and Methods: This retrospective study included 21 patients with metastatic BC and MPE who were hospitalized at the Clinic for Thoracic Surgery, University Clinical Center Niš, during 2023. The success of TP was assessed using predefined clinical and radiographic criteria.Results: TP was successful in 15 patients (71.4%). Luminal B BC was the most common subtype (42.9%). In the majority of cases, MPE was serous (71.4%) and ipsilateral (61.9%) to the primary breast tumor. Pleural cytology was positive in 28.6% of cases.Conclusion: TP is an effective treatment for breast cancer-caused MPE. MPE is predominantly associated with Luminal B BC, and patients typically present with ipsilateral, serous MPE.
Keywords: malignant pleural effusion; breast cancer; thoracic drainage; talc pleurodesis